2019
DOI: 10.3329/bjog.v33i1.43270
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Cervical Intraepithelial Neoplasia (CIN) at Khulna Division of Bangladesh

Abstract: Back ground: Cervical cancer is the most common genital tract cancer and the important cause of cancer death among Bangladeshi women. Information about actual number of women living with preinvasive phase of cervical cancer and their diagnosis and treatment is limited. For strengthening the programme and policy for cervical cancer prevention , the baseline prevalence of cervical intraepithelial neoplasia ( CIN) need to be assessed. Methods: This population based study aimed to determine the prevalence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…This underestimation of HPV prevalence in this study is most likely due to the study methodologies. The prevalent genotypes of HPV among CIN cases of current study were HPV 16,18,31,33,35,52, 56 and 58 either as single or multiple infections. A prospective study from Varnasi and adjoining areas of India reported that HR HPV 16,18,31,33,35,45,58,86 were observed among CIN cases and cervical cancer cases [39].…”
Section: Discussionmentioning
confidence: 65%
See 4 more Smart Citations
“…This underestimation of HPV prevalence in this study is most likely due to the study methodologies. The prevalent genotypes of HPV among CIN cases of current study were HPV 16,18,31,33,35,52, 56 and 58 either as single or multiple infections. A prospective study from Varnasi and adjoining areas of India reported that HR HPV 16,18,31,33,35,45,58,86 were observed among CIN cases and cervical cancer cases [39].…”
Section: Discussionmentioning
confidence: 65%
“…The prevalent genotypes of HPV among CIN cases of current study were HPV 16,18,31,33,35,52, 56 and 58 either as single or multiple infections. A prospective study from Varnasi and adjoining areas of India reported that HR HPV 16,18,31,33,35,45,58,86 were observed among CIN cases and cervical cancer cases [39]. In Pakistan, the prevalent genotypes in cervical cancer were HPV 16,18,45,56,73.…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations